UNIT ELECTRICITY PRODUCTION ANALYSIS OF GAS TURBINES ON PART LOAD - Erdem, Hasan Huseyin }; Sevilgen, Suleyman Hakan; Akkaya, Ali Volkan; Cetin, Burhanettin (YILDIZ TECHNICAL UNIV, 2005)
Gas turbine systems are one of the most preferred systems in the distributed power production. The most used gas turbines are simple one shaft gas turbines because these type gas turbines are simple and have low investment costs. In this study, unit electricity production costs on the part load of the simple gas turbines producing 5 MW power, which have different design parameters, have been computed. Levelized cost method has been used in the cost calculation. Furthermore, the parameters effects on unit electricity production costs have been investigated. As a conclusion, it has been demonstrated that unit electricity production costs on the part and full load for a certain power have been a decisive factor in the selecting power production plant.
Keywords: Levelized cost method; Electricity production cost; Gas turbine; Engineering